Ligand engineering of Au44 nanoclusters for NIR-II luminescent and photoacoustic imaging-guided cancer photothermal therapy. Issue 16 (3rd April 2023) - Yang, Ge; Mu, Xueluer; Pan, Xinxin; Tang, Ying; Yao, Qiaofeng; Wang, Yaru; Jiang, Fuyi; Du, Fanglin; Xie, Jianping; Zhou, Xianfeng; Yuan, Xun
Abstract : A theranostic probe was developed by conjugating NIR-II emitting Au44 MBA26 nanoclusters with photothermal Cy7 molecules via click chemistry, achieving NIR-II luminescent and photoacoustic imaging-guided cancer photothermal therapy. Abstract : Developing a high-performance noninvasive probe for precise cancer theranostics is very challenging but urgently required. Herein, a novel Au nanoclusters (NCs)-based probe was designed for cancer theranostics via ligand engineering by conjugating photoluminescent (PL) Au44 NCs in the second near-infrared window (NIR-II, 1000–1700 nm) with aromatic photoacoustic (PA)/photothermal molecules through click chemistry. This design bypasses the incompatibility dilemma between photoluminescence (PL) attributes and PA/photothermal properties because the rigidity of the PA/photothermal molecules can lead to aggregation-induced emission (AIE) of the Au(i )-ligand shell of the Au NCs by constraining their nonradiative relaxation. Benefiting from strong NIR-II PL with emissions at 1080 and 1240 nm, high photothermal conversion efficiency (65.12%), low cytotoxicity, appropriate renal clearance, and enhanced permeability and retention (EPR) effect, the as-designed Au NC-based theranostic probe achieves ultradeep NIR-II PL/PA imaging-guided cancer photothermal therapy (PTT). Remarkably, 16 days after photothermal treatment guided by NIR-II PL/PA imaging, mice were all healed without tumor recurrence, while the average life span of the mice in the control groups was only 17–21 days. This study is interesting because it provides a paradigm for designing a metal NC-based theranostics probe, and it may add fundamentally and methodologically to noninvasive imaging-guided disease therapy.